Enhancement of innate immune responses in Nile tilapia (Oreochromis niloticus) by dietary green-synthesized nanoparticles - Ferdous, Jannatul; Kundu, Goutam Kumar; Begum, Mahmuda; Zahid, Md Al; Khan, M Nuruzzaman; Hossain, Anwar; Hosen, Md Ismail; Mamun, Abdullah-Al; Mandal, Shankar Chandra (Dhaka University Journal of Biological Sciences, 2025)
This study evaluated the impact of dietary green-synthesized nanoparticles on innate immune responses in Nile tilapia (Oreochromis niloticus). Plant-based Zinc, selenium, copper, and manganese nanoparticles were incorporated into diets at 30 mg/kg and 60 mg/kg concentrations and administered over a 28-day feeding trial. The expression of some selected important immune genes, including IL-1β, IL-10, TLR3, IRF3, viperin, and TGF-β, was assessed in gill and liver tissues using quantitative real-time PCR. Fish fed nanoparticle supplemented diets exhibited significant upregulation of pro-inflammatory (IL-1β), anti-inflammatory (IL-10, TGF-β), and antiviral (TLR3, IRF3, viperin) genes compared to the control group (p < 0.05). Gene expression exhibited dose and time dependent patterns showing significant upregulation as early as day 7 and sustained until days 14, 21, and 28, particularly at the higher supplementation dose (60 mg/kg). These results suggest that green-synthesized nanoparticles can modulate innate immunity by enhancing both inflammatory and regulatory pathways, promoting immune preparedness without apparent adverse effects. The findings support the potential application of plant-based nanoparticles as eco-friendly immunostimulants in aquaculture, offering a promising alternative to antibiotic use. Dhaka Univ. J. Biol. Sci. 34(2): 117-137, 2025 (July)